Pemetaan Spasial Emisi Gas Karbon Dioksida (CO2) Akibat Penggunaan LPG Pada Kawasan Permukiman Di Kecamatan Aur Birugo Tigo Baleh Kota Bukittinggi - Hidayat, Rahmad; Purwaningsih, Endah (JURNAL BUANA, 2026)
Carbon dioxide gas (CO2) is easy to find in everyday life, one of which is LPG gas which is used as household cooking fuel. The gas evaporates and spreads quickly so that the combustion produced by the use of LPG gas produces carbon dioxide (CO2) which will have an impact on global warming. The purpose of this study is to determine emissions and spatial emission factors (FES) which are used as a reference to determine the level of distribution of carbon emissions in each region so that it can provide an overview of the contribution of LPG gas consumption and the distribution level of carbon dioxide (CO2) emissions in the Residential Area of ​​Aur Birugo District. Tigo Baleh, Bukittinggi City. This research uses the type of data with quantitative analysis and then calculated using the method from the Intergovernmental Panel on Climate Change (IPCC 2006). The result of the calculation of each household using fuel for cooking is 11,055.74 tons of CO2/year.